Karakteristik Tanah Longsor di Daerah Aliran Sungai Tangka - Usman Arsyad; Roland Alexander Barkey; Wahyuni Wahyuni; Karla Kembongallo Matandung (Jurnal Hutan dan Masyarakat, 2018)
Landslides occur as a result of ground movement on steep slopes, and the high humidity (moisture), and the sparse vegetation (open land). The Local conditions is an interrelated components. The process of landslides can be explained that the water soak into the soil will add weight to the ground. If the water penetrates the soil acts as a watertight sliding plane, the ground becomes slippery and soil weathering on it will move to follow the slope. This study aims to determine the type of landslide, landslide characteristics and landslides causing factors. This research was conducted in September 2015 in Watershed Tangka. The study consisted of three stages, namely the determination of the coordinates of the location of the landslide, landslide determining the location of the sample, the determination of the type of landslide, slope measurements, measurements of the dimensions of landslide and infiltration. Research results obtained are the coordinates of the location of as many as 17 points landslide, landslide types of translation and rotation, land cover and soil texture. There is no difference in the type of soil, infiltration rate, vegetation, geologi, slope and rainfall in both types of landslide are found.